Perception of Tourism Satisfaction: A Study at Blimbingsari Tourism Village in Bali - Gusti Ngurah Joko Adinegara (Faculty of Economics, Universitas Sriwijaya, 2019)
Blimbingsari tourism village has decreased in the number of tourist visits, even though the potential of tourist attractions offered is increasingly diverse. This situation is a major concern for managers in an effort to increase visiting tourists. The purpose of this study was to analyze the service quality attributes considered important by tourists as well as the perceived performance they felt when visiting. The sample size is 99, which consist of both domestic and foreign tourists. Importance Performance Analysis (IPA) is used in order to identify service quality attributes. The results show that there is a gap between the level of importance and performance of service quality attributes. Based on cartesian diagram, it is found that there is one attribute in concentrate here quadrant which is the main priority to be improved. These attribute is the experience of trekking, hiking, bird watching, and local activities. Based on the results obtained of customer satisfaction index, service qualities that have been given are on criteria quite satisfactory. The results of this analysis can help the village and tourism management staff in improving the service quality of tourists in terms of service, accommodation and cuisine. Research recommendations are also discussed to obtain more comprehensive results in measuring the satisfaction of tourists when visiting tourism village destination.